Finding of a skull of Pseudorca crassidens in Caleta de Los Loros, Rio Negro Province, Argentina - Bustos, Raimundo Lucas; Negri, Maria Fernanda; Daneri, Gustavo Adolfo; Varela, Esperanza Amalia; Luna, Marcos Javier (Latin American Journal of Aquatic Mammals)
The false killer whale, Pseudorca crassidens, exhibits one of the widest and most continuous distributions among cetaceans. However, basic information about its biology is poorly known due to the low frequency of sightings and its offshore habits. Moreover, most of the knowledge on this species has been obtained from stranded animals. On 3 March 2012, in the proximity of a colony of South American sea lions (Otaria flavescens) located at Caleta de los Loros, Río Negro Province, Argentina (40o59’S, 64o14’W), a cetacean skull was found in the intertidal zone. The specimen was later identified as P. crassidens. The present note reports a new record of false killer whale in the continental shelf waters of Argentina and provides new data on the distribution and skull morphometrics of the species. Fil: Bustos, Raimundo Lucas. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Negri, Maria Fernanda. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Daneri, Gustavo Adolfo. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Varela, Esperanza Amalia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Luna, Marcos Javier. Provincia de Río Negro. Secretaría de Medio Ambiente y Desarrollo Sustentable; Argentina